PENERAPAN TEKNOLOGI PEMBUATAN PUPUK ORGANIK BERBENTUK KOMPOS DAN CAIR DARI SERASAH DAUN LAMUN DI RUMAH TANGGA NELAYAN DESA TAPULAGA KABUPATEN KONAWE SULAWESI TENGGARA - Ishak, Ermayanti; Asriyana, Asriyana; Hamid, Abdul; Halili, Halili; Bahtiar, Bahtiar; Jali, Wa (Universitas Mataram, 2024)
The seagrass meadow ecosystem along the coast of Tapulaga Village plays a crucial role in the nutrient cycle in the marine environment. The photosynthesis process transforms carbon dioxide into carbohydrates, which are stored in the tissues of seagrass, resulting in sucrose production. The availability and content of seagrass leaf litter trapped in fishermen's fish traps initiated a community service activity integrated with thematic real-work lectures (KKN). The focus of this activity is on fulfilling balanced nutrition, aiming to increase the interest of fishing families in consuming vegetables. The objective of the community service is to promote balanced nutrition by diversifying food consumption with various vegetables grown on their own land, using compost and organic fertilizer derived from seagrass leaf litter. The method used is the Takakura method, which involves composting organic waste using a composter with holes. Organic waste is placed in the composter and EM4 (decomposer bacteria) and molasses are added. Stirring is done daily to accelerate the waste decomposition process. Organic liquid fertilizer is produced by utilizing the liquid from the composter. The results show that vegetable plants grown in compost and treated with organic liquid fertilizer from seagrass leaf litter exhibit good growth and can be harvested on the 18th day. The use of seagrass leaf litter as a raw material for making compost and organic liquid fertilizer has a significant impact on vegetable plant growth. The community service activity had a positive effect on the fisherwomen, including their strong determination to apply this planting method at home and their increased interest in consuming vegetables as part of their daily meals.